Phenolic compounds and rare polyhydroxylated triterpenoid saponins from Eryngium yuccifolium - Zhang, Z.; Li, S.; Ownby, S.; Wang, P.; Yuan, W.; Zhang, W.; Scott Beasley, R.
Phytochemical investigation on the whole plant of Eryngium yuccifolium resulted in the isolation and identification of three phenolic compounds (1-3)and 12 polyhydroxylated triterpenoid saponins, named eryngiosides A-L (4-15), together with four known compounds aempferol-3-O-(2,6-di-O-trans-p-coumaroyl)- b-D-glucopyranoside (16), caffeic acid (17), 21b-angeloyloxy-3b-[b-D-glucopyranosyl-(1?2)]-[b-D-xylopyranosyl-(1?3)]-b-D-glucuronopyranosyloxyolean-12-ene-15a,16a,22a,28-tetrol (18), and saniculasaponin III (19). This study reports the isolation of these compounds and their structural elucidation by extensive spectroscopic analyses and chemical degradation
Keywords: ERYNGIUM YUCCIFOLIUM; APIACEAE; TRITERPENOID SAPONINS; PHENOLIC COMPOUNDS; ERYNGIOSIDES A-L; CAMELLIAGENIN A; A1-BARRIGENOL; R1-BARRIGENOL